How do increasing background concentrations of tropospheric ozone affect peatland plant growth and carbon gas exchange?. (February 2016) - Williamson, Jennifer L.; Mills, Gina; Hayes, Felicity; Jones, Timothy; Freeman, Chris
Abstract: In this study we have demonstrated that plants originating from upland peat bogs are sensitive to increasing background concentrations of ozone. Peatland mesocosms from an upland peat bog in North Wales, UK were exposed to eight levels of elevated background ozone in solardomes for 4 months from May to August, with 24 h mean ozone concentrations ranging from 16 to 94 ppb and cumulative AOT024hr ranging from 45.98 ppm h to 259.63 ppm h. Our results show that plant senescence increased with increasing exposure to ozone, although there was no significant effect of increasing ozone on plant biomass. Assessments of carbon dioxide and methane fluxes from the mesocosms suggests that there was no change in carbon dioxide fluxes over the 4 month exposure period but that methane fluxes increased as cumulative ozone exposure increased to a maximum AOT 024hr of approximately 120 ppm h and then decreased as cumulative ozone exposure increased further. Highlights: Peatland plant senescence is increase by season-long exposure to elevated ozone. Vascular plant and moss biomass is not affected by ozone exposure. Methane emissions increase at low to moderate cumulative ozone exposure. Further increases in cumulative ozone exposure decrease methane emissions. Dissolved organic carbon in the peat pore water is not affected by ozone exposure.